The genus Rhynchoglossum Blume (Gesneriaceae) in Thailand - Pattharahirantricin, Nannapat (Thai Forest Bulletin (Botany), 2014)
The genus Rhynchoglossum Blume in Thailand is revised. Three species are recognised, R. obliquum Blume, R. mirabilis Patthar. and R. saccatum Patthar., the latter two newly described here and endemic to Thailand. A key to the species and illustrations are provided.